2017
DOI: 10.1002/mop.30618
|View full text |Cite
|
Sign up to set email alerts
|

Inverse E‐shape chiral metamaterial for long distance telecommunication

Abstract: In this article, a chiral metamaterial based on the inverse E‐shape combined with the outer ring resonator that look like an inverse E‐shape structure has been discussed. The designed metamaterial structure is printed on Rogers RT 5880 material and electromagnetic simulator CST Microwave Studio has been used to design, simulation and investigation purposes. The proposed structure shows resonance at C‐band and exhibits 5.14 GHz bandwidth from 4 to 9.14 GHz. The effective medium ratio of the designed metamateria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…The designed MTM shows the beam steering properties, whereas no other references displayed the beam steering in the references. The exhibited bandwidth is 4.49 GHz, whereas only Hasan et al showed wide bandwidth compared with the designed one. The proposed MTM single unit cell is more compact with respect to other unit cells.…”
Section: Results Analysismentioning
confidence: 74%
See 2 more Smart Citations
“…The designed MTM shows the beam steering properties, whereas no other references displayed the beam steering in the references. The exhibited bandwidth is 4.49 GHz, whereas only Hasan et al showed wide bandwidth compared with the designed one. The proposed MTM single unit cell is more compact with respect to other unit cells.…”
Section: Results Analysismentioning
confidence: 74%
“…A 3D optical MTM had been constructed a prism to demonstrate negative refractive index at optical frequencies with a very high figure of merit of 3.5 and the negative index existing over a broad spectral range in Valentine et al Again, a chiral MTM had been printed on Rogers RT 5880 material, which showed resonance at C‐band and exhibited 5.14 GHz bandwidth from 4.0 to 9.14 GHz. Due to the bandwidth in the major portion of C‐band, the proposed chiral MTM was applicable for telecommunication applications . Further, a MTM design that enhanced nonlinear response with strong artificial magnetism, ensures a negative refractive index with bistable and self‐tunable response at 2011 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Untuk aplikasi gelombang milimeter satu antena tampalan fraktal boleh dikonfigurasi dua band dicadangkan untuk menunjukkan kekerapan operasi yang serupa tetapi corak radiasi yang berlainan antara urutan sifar dan mod resonan pesanan +1 (Yan et al 2006). Struktur metabahan lengan kiri berdasarkan bentuk E songsang digabungkan dengan penyalun cincin luar yang dicetak pada bahan Rogers RT 5880 yang dicadangkan, yang menunjukkan resonan pada band C dan lebar jalur 5.14 GHz dari 4.0 hingga 9.14 GHz (Hasan et al 2017). Antena dwikutub yang boleh dikonfigurasi dicadangkan untuk aplikasi 5G yang dikendalikan oleh suis dalam tampung persegi.…”
Section: Pengenalanunclassified
“…Therefore, due to these unique properties and for enhancing the performance of the antennas nowadays metamaterial antennas have become a research hotspot. Recently, a lots of dual- and triple-bands metamaterial (MMs) structure 1,2 with metamaterial antennas have discussed in research articles. Metamaterial antenna is a class for antenna inspired by metamaterial structure on radiating patch or ground plane for better performances.…”
Section: Introductionmentioning
confidence: 99%